Perbandingan Pencatatan Keuangan Manual dengan Menggunakan Zahir Accounting Pada Warung Kopi Rakjat - Maulidia, Elsa; Wasiyanti, Sri; Miharja, Kasmanto (Akasia: Artikel Ilmiah Sistem Informasi Akuntansi, 2023)
Warung Kopi Rakjat is a company operating in the trading business which provides various types of drinks. Currently Warung Kopi Rakjat has a problem, namely the sales recording system which is still manual by writing down transactions using books, many obstacles are faced such as transactions that are not recorded, sales recaps take a long time and financial reporting is often late. This problem is the background for this research to change manual transaction recording by implementing accounting software, namely Zahir Accounting Version 6 Build 13, in managing financial data. Using Zahir makes it easy and has many advantages in its operation, namely using Indonesian, a user guide that is easy to follow and other facilities in Zahir. By using Zahir, companies will certainly gain benefits in managing financial data, storing financial data. And obtain comprehensive financial reports in a short time with correct data.